Change in grip strength, hang time, and knot tying speed after 24 hours of endurance rock climbing - Yu, Elaine; Lowe, Jacques; Millon, Jasmin; Tran, Kristi; Coffey, Christanne (Frontiers in Sports and Active Living, 2023)
Background Non-professional climbers are increasingly attempting long routes in a single day. Many suffer injury or rely on search and rescue teams when they become too fatigued to finish. Predicting fatigue is difficult, and existing studies have only studied climbers over durations less than an hour, while many outdoor multipitch climbs require more than an hour of climbing. Objectives To determine how strength, endurance, and dexterity reflect fatigue after 24 h of continuous climbing. Methods Volunteer competitors completed measurements of grip strength, static hang time to failure, and time to tie a figure-eight follow-through knot. Measurements were taken during the registration period before the competition and again within an hour after the competition ended. Measurements were compared using the paired t-test. Subgroup analysis was applied to competitors by division. Linear regression was applied to determine the relationship between vertical feet climbed and the number of routes climbed during the competition on each metric. Results Thirty-six total climbers (average age 29.4 years old) completed pre- and post-competition measurements. After 24 h of climbing (n = 36), mean grip strength decreased by 14.3–15 lbs or 14.7%–15.1% (p < 0.001) and static hang time decreased by 54.2 s or 71.2% (p < 0.001). There was no significant change in time to tie a figure-eight-follow-through knot. Grip strength and hang time decreases were significant in climbers with outdoor redpoints of 5.10a and above. Hang time decreased by 5.4 s per 1,000 vertical feet climbed (p = 0.044). Conclusion Climbers can expect to experience a 14.7%–15.1% decrease in grip strength and 71.2% decrease in static hang time after 24 h of continuous climbing. These changes may make it difficult to climb consistently over a long objective, and climbers can use these measures at home to train for longer climbing routes. Future studies on shorter climbing intervals can help determine rates of decline in performance measures.